Penerapan Konseling Behavioral Dengan Teknik Pemodelan Sebaya Untuk Mengurangi Kecenderungan Perilaku Prokrastinasi Akademik Siswa - David Ari Setyawan (Guidance : Jurnal Bimbingan dan Konseling, 2021)
This study contains an effort to reduce the tendency of students' academic procrastination behavior by applying behavioral counseling with peer modeling techniques. Techniques have great potential to run effectively and get maximum results. Because students in a school environment will tend to be easy to imitate the behavior of their peers. Peer modeling techniques will position students as observers who will observe other students as modeling objects. The aspect observed by the client is how the pattern of life and discipline applied by students is used as an object. The client will observe and then try to apply it in his life. The advantage of this technique is that the client will be more flexible and flexible in observing the object, because the object is his own friend. Observation results will also be more flexible because the object can be varied so that it can be adjusted to the client's self. In handling it, the application of counseling with peer modeling techniques is a potential solution. The role of the environment in this technique makes the client free to explore and observe the modeling object that has been determined. Accurate and maximum results will be obtained if the counselor, client and also the steps taken are appropriate and coherent. The research subjects were students of class IX MTs NU Mranggen for the 2020/2021 school year. The methods used in collecting data were questionnaires, interviews and observations. The result obtained in the first cycle were still medium, is namely 51% of the success indicator, while the second cycle is in the low category with a score 30%, so it can be concluded that peer modeling is effective in reducing academic procrastination.